RELATIONS OF LARYNGOTRACHEITIS AND RECURRENT LARYNGOTRACHEITIS IN CHILDREN WITH WEATHER CONDITIONS - Станіславчук, Л.М.; Попенко, Н.А. (World of Medicine and Biology, 2014)
It was analyzed the incidences of laryngotracheitis (LT) and recurrent laryngotracheitis (RLT) in children of Vinnytsya city between 2000-2004 in connection with medical types of weather. The term «LT» was used in the case of 1-3 episodes of the disease in a patient, the term «RLT» - in the case of 4 or more episodes. During the observation period (1827 days) there were registered 1499 cases of LT and 92 cases of RLT in children. The number of daily emergency department calls in cases of LT ranged from 0 to 6, in cases of RLT - from 0 to 2.It was analyzed synoptic maps, such meteorological factors (MF) as air temperature, air pressure, relative air humidity, partial pressure of water vapor in air, oxygen content in air, wind speed and wind direction, and the changes of meteorological parameters from day to day. Medical typification of weather was performed according to weather classification of V.F. Ovcharova et al. (stable and indifferent type of weather, unstable weather with transition of indifferent weather in spastic type of weather, spastic type of weather, unstable weather of spastic type with elements of weather of hypoxic type, hypoxic type of weather, unstable weather of hypoxic type with elements of weather of spastic type, transition of weather of spastic type in stable and indifferent type of weather). Biotropism to each type of weather was evaluated according to recommendations of V.G.Bardov by determining the extent of changes of meteorological parameters (average air temperature, average air pressure, average relative air humidity, average partial pressure of water vapor in air, average oxygen content in air) from day to day. Periods of maximal and minimal circulation of respiratory viruses have been identified as a result of long-term monitoring of the dynamics of respiratory viruses circulation (influenza viruses, parainfluenza viruses, adenoviruses, respiratory syncytial viruses).A direct correlation of RLT (p
Keywords: laryngotracheitis; recurrent laryngotracheitis; medical types of weather; children